Resting-state and vocabulary tasks distinctively inform on age-related differences in the functional brain connectome. Issue 8 (14th September 2019) - Ferré, Perrine; Benhajali, Yassine; Steffener, Jason; Stern, Yaakov; Joanette, Yves; Bellec, Pierre
ABSTRACT: Most of the current knowledge about age-related differences in brain neurofunctional organisation stems from neuroimaging studies using either a "resting state" paradigm, or cognitive tasks for which performance decreases with age. However, it remains to be known if comparable age-related differences are found when participants engage in cognitive activities for which performance is maintained with age, such as vocabulary knowledge tasks. A functional connectivity analysis was performed on 286 adults ranging from 18 to 80 years old, based on resting state or vocabulary tasks. Increases in connectivity of regions of the language network were observed during task completion. Conversely, only age-related decreases were observed during resting-state. While vocabulary accuracy increased with age, no interaction was found between functional connectivity, age and task accuracy or proxies of cognitive reserve, suggesting that older individuals typically benefits from semantic knowledge accumulated throughout one's life trajectory, without the need for compensatory mechanisms.